STRATEGY EMPOWERMENT WEED SCAVENGERS AND WEED CRAFTSMEN THROUGH A "HOLISTIC DEVELOPMENT" APPROACH - Ade Sadikin Akhyadi; Rika Fitri Ramadani; Holva Lovana Siregar (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
This research departs from the various empowerment strategies implemented in each community empowerment agency. Heterogeneous environmental conditions become a consideration in implementing empowerment strategies to the community. The empowerment strategy becomes the main capital to attract the attention of the community to take the empowerment program seriously. Cooperatives are a forum for community empowerment in the economic field. This research was conducted because there is a uniqueness found in the empowerment program. This institution of empowerment does not only empower the community economically but also socially, environmentally and spiritually. This study uses qualitative methods of observation, interviews, and documentation studies. The findings of this study are empowerment strategies using Holistic Development which in turn is able to develop community life dimensions in an integrated manner so as to make the community independent and prosperous.